HUBUNGAN PENCAPAIAN PANDU PTM DENGAN DIABETES (ANALISIS RISKESDAS 2018 DAN PROFIL KESEHATAN 2018) - Saini, Izzatul Mardiah; Misana, Fatima Nur; Bagus, Nurzahara; Siregar, Kemal N (Politeknik Kesehatan Kemenkes Malang, 2023)
Background: Non-communicable disease (NCD) has been the leading cause of death in Indonesia. To prevent that, the government of the Republic of Indonesia made some policies that resulted in programs such as Pandu PTM. Pandu PTM is an approach for early detection and monitoring of NCD risk factors which is integrated and done through Posbindu PTMAims: This research aims to know the relationship between the implementation of Pandu PTM with the incident numbers of diabetes melitus in IndonesiaSubjects and Method: This research was done through March—April 2023. This research was done through observational analytic design with an ecological study approach. The samples used were the 34 provinces of Indonesia. The data being used was secondary data which was obtained from Riset Kesehatan Dasar (Riskesdas) 2018 and Health Profile Year 2018. The independent variable was the achievement of Pandu PTM in percent and the dependent variable was the diabetes melitus prevalence. The data was then analyzed using simple linear regressionResults: The result shows that there was no relationship between Pandu PTM implementation with diabetes melitus incident number in Indonesia (p-value= 0,067)Conclusion: The implementation of Pandu PTM was not supported by expert health workers and there was still little awareness among the society. It was suggested to increase the expertise of health workers and increase people’s awareness of the importance of early detection of NCD risk factors.